2015
DOI: 10.1007/s11571-015-9333-5
|View full text |Cite
|
Sign up to set email alerts
|

EEG gamma-band activity during audiovisual speech comprehension in different noise environments

Abstract: The presence of cross-modal stochastic resonance in different noise environments has been proved in previous behavioral and event-related potential studies, while it was still unclear whether the gamma-band oscillation study was another evidence of cross-modal stochastic resonance. The multisensory gain of gamma-band activity between the audiovisual (AV) and auditory-only conditions in different noise environments was analyzed. Videos of face motion articulating words concordant with different levels of pink n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The authors found suppression of central beta-band power, which was modulated by concurrent noise stimulation. A further study, which examined noise during audiovisual speech perception, has also highlighted the role of early gamma-band oscillations (Lin and others 2015). The study revealed that auditory noise increases early induced and evoked gamma power, as well as ITC at frontal electrodes.…”
Section: Audiovisual Speech Processingmentioning
confidence: 99%
“…The authors found suppression of central beta-band power, which was modulated by concurrent noise stimulation. A further study, which examined noise during audiovisual speech perception, has also highlighted the role of early gamma-band oscillations (Lin and others 2015). The study revealed that auditory noise increases early induced and evoked gamma power, as well as ITC at frontal electrodes.…”
Section: Audiovisual Speech Processingmentioning
confidence: 99%
“…EEG measures the mental activity of the brain directly from the scalp while performing a given cognitive task. The neuronal oscillations related to speech perception and speech comprehension have been identified as theta and gamma frequency bands (Ghitza and Greenberg 2009;Ghitza 2013;Lin et al 2015). Brain regions associated with speech and imagined speech are identified as homunculus, Broca's area and Wernicke's area (Hickok and Poeppel 2000;Poeppel and Hickok 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at the high SNR auditory information was sufficient for human brain to identify speech, while visual information was less utilized, which made the audio-visual speech recognition rate be similar to that of audio-only. On the other hand, the auditory information was weak at the low SNR, and the visual information was relatively strong, which made the audio-visual speech recognition rate be similar to that of the visual-only condition [25,26] .…”
Section: Comparison Of Speech Recognition Ability Between Different Modalitiesmentioning
confidence: 99%